Penerapan Diversi Terhadap Tindak Pidana Tanpa Korban (Tindak Pidana Narkotika) Yang Dilakukan Oleh Anak - Anam, Fahrun; Moonti, Roy Marthen; Kadir, Yusrianto; Kasim, Muslim (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The purpose of the research is to know and analyze the application of diversion to victimless criminal acts (narcotics) committed by children in Marisa District Court and to know and analyze the factors that influence the application of diversion to minors in Marisa District Court, Pohuwato Regency. The type of research used is normative-empirical legal research which basically combines a normative legal approach with the addition of various empirical elements. The implementation of diversion for victimless crimes is still less effective because there are still obstacles such as the absence of a special diversion room at the Marisa District Court, even though diversion is an important step in handling narcotics cases involving children and there are several factors related to the diversion process including the lack of adequate regulations in regulating the implementation of diversion for victimless crimes in the examination process in court, in the case of handling children in conflict with the law it should not only be the police, prosecutors, or juvenile judges who must have special qualifications related to handling children in conflict with the law who can handle the case, besides that the lack of understanding of the parties about the implementation of diversion.